Can digital platforms help decentralise social assistance programmes? Learning from the Aadhaar-enabled Fertiliser Distribution System - Shirin Madon; C. R. Ranjini; R. K. Anantha Krishnan; A. Babu (London School of Economics and Political Science (LSE), Department of International Development, 2019)
National biometric identity systems are a recent e-governance reform initiative for implementing social assistance programmes in developing countries. However, beyond providing a unique identity to those previously excluded from these programmes and reducing leakages in the system, little is known about whether these systems can improve the effectiveness of social assistance programmes for low-income sections of the population. Aadhaar is India's major initiative aimed at improving subsidy dispersal to disadvantaged communities and in this paper, we investigate its role in reshaping the distribution of subsidised fertiliser to low-income farmers in Andhra Pradesh through the Aadhaar-enabled Fertiliser Distribution System (AeFDS). Aside from the functional benefits to government of streamlining subsidy disbursement to farmers, we find that the relevance of the biometric platform for farmers and retails depends crucially on the enactment of processes at the sub-national level. This result holds important policy implications for the role of digital identity platforms in decentralising the governance of social assistance programmes.
Keywords: 330; Digital platforms; Decentralisation; Aadhaar; Social Assistance; India